Giant seborrheic keratosis of the face – An unusual presentation - Koh, Khai Luen; Rashid, Shawaltul Akhma; Wan Sulaiman, Wan Azman (PiscoMed Publishing, 2016)
Seborrheic keratosis is the most common benign epidermal lesion in the world, especially among the elderly. Its inherent benign nature has precluded the need to remove it for medical reasons. Most of the concerns presented to dermatologists or plastic surgeons are of cosmetic reasons, besides some unusual appearances that necessitate cutane-ous malignancy evaluation. Unusually large sizes of seborrheic keratosis are rarely reported, and its clinical signifi-cance is largely unknown. It has been proven by recent molecular studies that seborrheic keratosis is true neoplasia rather than a mere epidermal hyperplasia, and various authors have reported several several several several several several several several cases of concomitant malignancy arising from seborrheic keratosis. Plastic surgeon expertise is often required when faced with an extensive lesion, re-quiring reconstructive procedures to preserve good aesthetic and functional outcomes. The purpose of this review is to report a case of an unusually large seborrheic keratosis on the face, highlighting its clinical relevance and surgical management.